Diseño y simulación de controladores por aprendizaje reforzado para convertidores de potencia utilizados en micro redes de corriente directa. (2023)
This project presents a proposal which is associated with the research project "Energy management based on cloud computing for interoperability between a group of isolated microgrids" financed by Min Ciencias. The main objective of this project is to design, implement and validate intelligent control techniques for stepdown (Buck) power converters and boost (Boost) power converters used in direct current microgrids.